Hydrogen and Halogen Bonding in Homogeneous External Electric Fields: Modulating the Bond Strengths. Issue 56 (26th August 2021) - Chen, Li; Dang, Jingshuang; Du, Juan; Wang, Changwei; Mo, Yirong
Abstract: Recent years have witnessed various fascinating phenomena arising from the interactions of noncovalent bonds with homogeneous external electric fields (EEFs). Here we performed a computational study to interpret the sensitivity of intrinsic bond strengths to EEFs in terms of steric effect and orbital interactions. The block‐localized wavefunction (BLW) method, which combines the advantages of both ab initio valence bond (VB) theory and molecular orbital (MO) theory, and the subsequent energy decomposition (BLW‐ED) approach were adopted. The sensitivity was monitored and analyzed using the induced energy term, which is the variation in each energy component along the EEF strength. Systems with single or multiple hydrogen (H) or halogen (X) bond(s) were also examined. It was found that the X‐bond strength change to EEFs mainly stems from the covalency change, while generally the steric effect rules the response of H‐bonds to EEFs. Furthermore, X‐bonds are more sensitive to EEFs, with the key difference between H‐ and X‐bonds lying in the charge transfer interaction. Since phenylboronic acid has been experimentally used as a smart linker in EEFs, switchable sensitivity was scrutinized with the example of the phenylboronic acid dimer, which exhibits two conformations with either antiparallel or parallel H‐bonds, thereby, opposite or consistent responses to EEFs. Among the studied systems, the quadruple X‐bonds in molecular capsules exhibit remarkable sensitivity, with its interaction energy increased by −95.2 kJ mol −1 at the EEF strength 0.005 a.u. Abstract : The sensitivity of single and multiple hydrogen (H) and halogen (X) bonding to external electric fields (EEFs) was analyzed. Computations show that the variations of X‐bonds mainly stem from the covalency change, while generally the steric effect governs the response of H‐bonds to EEFs. X‐bonds are more sensitive to EEFs, with the key difference from H‐bonds lying in the charge transfer interaction. The sensitivity in multiple‐bonding cases can be regulated by the permutations of noncovalent interactions.